Radiographers' self-perceived competencies after attending postgraduate courses in CT and MRI. Issue 3 (August 2022) - Chaka, B.; Adamson, H.; Foster, B.; Snaith, B.
Abstract: Introduction: Postgraduate education in computed tomography (CT) and magnetic resonance imaging (MRI) varies globally. Multiple factors affect the development of associated core skills and competencies for these specialist roles. Previous research has highlighted that different teaching standards and methods may influence radiographers' confidence and competencies. Nonetheless, there is limited knowledge of skill development and capabilities in post-registration roles. Hence, the aim of this research was to explore radiographers' self-perceived competencies before, during and after successful completion of postgraduate study. Methods: Radiographers enrolled on the CT and MRI courses voluntarily completed questionnaires at three time points. As part of the last survey, questions were added to evaluate their perceptions of the courses' impact on their clinical and professional practice. Descriptive statistics, Wilcoxon matched pairs signed rank and Friedman tests, were performed to analyse results across the different time points. Results: 53 students completed the baseline survey, with initial perceived areas of weakness being lack of knowledge relating to CT or MR technology, cross-sectional anatomy and pathology. Follow up surveys, highlighted a significant increase in self-described competence in technical knowledge, literature appraisal and image viewing skills. As a result of completing the course, students described favourable changes to their departmental practices and their own continuing professional development (CPD). Challenges detailed included but not limited to lack of study time provided by employers, and the demands of balancing studies and work commitments. Conclusion: Postgraduate education has value and positively impacts radiographers and their clinical departments. The courses enabled the radiographers, including those experienced in CT and or MRI to develop skills they could translate into clinical practice, thereby contributing towards service delivery. Implications for practice: Post graduate education has the potential to enhance self-perceived competency in aspects of CT and MRI practice.